Respostas
respondido por:
0
8x - (4x -1) = 3
8x -4x +1 = 3
8x - 4x = 3 - 1
4x = 2
x = 2/4 x = 1/2
8x -4x +1 = 3
8x - 4x = 3 - 1
4x = 2
x = 2/4 x = 1/2
matheusx491owjnj6:
ta errado ;D
respondido por:
0
boa tarde Erika, resolvendo essa equação encontramos:
![8x - (4x - 1) = 3 \\ 8x - 4x + 1 = 3 \\ 4x + 1 = 3 \\ 4x = 3 - 1 \\ 4x = 2 \\ \\ \frac{4x}{4} = \frac{2}{4} \\ \\ x = 0.5 8x - (4x - 1) = 3 \\ 8x - 4x + 1 = 3 \\ 4x + 1 = 3 \\ 4x = 3 - 1 \\ 4x = 2 \\ \\ \frac{4x}{4} = \frac{2}{4} \\ \\ x = 0.5](https://tex.z-dn.net/?f=8x+-+%284x+-+1%29+%3D+3+%5C%5C+8x+-+4x+%2B+1+%3D+3+%5C%5C+4x+%2B+1+%3D+3+%5C%5C+4x+%3D+3+-+1+%5C%5C+4x+%3D+2+%5C%5C++%5C%5C++%5Cfrac%7B4x%7D%7B4%7D++%3D++%5Cfrac%7B2%7D%7B4%7D++%5C%5C++%5C%5C+x+%3D+0.5)
espero ter ajudado
bons estudos :D
espero ter ajudado
bons estudos :D
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás